Pembangunan Sistem Informasi Manajemen Kegiatan Tryout SBMPTN Berbasis Website - Thomas Ariyanto; Denny Sagita Rusdianto; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Currently the SBMPTN tryout has several changes such as eliminating the paper-based exam model and changing the scoring system. The latest scoring system uses the Item Response Theory method. The questions will be classified based on the difficulty level and given different weights. The survey results conducted by the author, from 50 respondents participating in the SBMPTN tryout, as many as 50% of respondents stated that they had never taken a computer-based tryout and as many as 68% of respondents said they had never taken a tryout with the latest scoring system. In its current implementation, some tryout organizers still use the paper based exam model with a manual registration system so they have to recap hundreds of registrant data manually. To overcome this problem, an information system for SBMPTN Tryout management is needed. This system can bring together organizers & participants in carrying out SBMPTN Tryout activities. Through this system, organizers can create and manage SBMPTN Tryouts with the computer-based exam model, with the latest scoring system. While for the participants, they can do the registration, payment & take the tryout test that they want . This system has 55 functional requirements and 1 non-functional requirement. The design to build this system is system architecture, sequence diagrams, class diagram, database, component and interfaces. The system has also been tested with 100% valid results for all test.